Sifat Kepribadian Narsistik, Ketidakjujuran Akademik, dan Persepsi Ketidakjujuran Profesional Mahasiswa Akuntansi - Trifena Michelle Jane Kristianto (Jurnal Akuntansi Bisnis, 2023)
Excessive desire to achieve high academic performance will lead to narcissism. Given the devastating effects of academic dishonesty and narcissistic behavior when students enter the workforce, it is important to study student negative behavior to detect and seek preventive measures so that it does not escalate into corrupt behavior. This study employed the Narcissistic Personality Inventory (NPI) introduced by Raskin and Terry. Two independent variables were used, namely Narcissistic Personality Traits and Academic Dishonesty. Sampel was selected from accounting students in Semarang with an A-accredited university. The results of this study indicate that narcissistic personality traits and academic dishonesty have a significant effect on perceptions of professional dishonesty in accounting students.